Condition Optimization And Production Of Extracellular L-Glutaminase From Pseudomonas Fluorescens - CHITANAND M.P.,; SHETE H.G., (International Journal of Pharma and Bio Sciences, 2012)
L-Glutaminase [L-Glutaminase amido-hydrolase, EC-3.5.1.2] is widely distributed in microorganisms including bacteria, yeast, and fungi. The enzyme has received greater attention and significance in pharmaceutical industry since it is recognized as having potent antitumor activity. The enzyme also has applications in food industries. In the present work an extra cellular L-glutaminase was produced from Pseudomonas fluorescens. The screening of extra cellular L-Glutaminase was done by dye based procedure on minimal agar medium. The conditions for production of glutaminase were optimized by studying the effect of incubation period and different carbon and nitrogen sources. The effect of temperature, pH and substrate concentration on L-glutaminase activity was studied. Maximum activity of enzyme was observed at 37 0C and at pH 8.